Cardiac Tamponade Diagnosed by Point-of-Care Ultrasound. Issue 2 (February 2017) - Smith, Austin T.; Watnick, Caroline; Ferre, Robinson M.
Abstract : Abstract: We present a case involving a 12-year-old boy who presented to the emergency department and was diagnosed with a pericardial effusion with tamponade physiology by point-of-care ultrasound. The diagnosis resulted in prompt treatment and definitive therapy.